Mobius Graphs - Vasumathi, N.; Vangipuram, S. (Journal of Informatics and Mathematical Sciences, 2009)
The study of graphs on natural numbers as its vertex set and with adjacency defined using tools of number theoretic functions is interesting and may focus new light on structure of the number systems. In this paper, we have studied the structure of finite graphs whose vertices are labeled with natural numbers and the adjacency is defined in terms of the well known Mobius function.